Dealing with Migrants in the Central Mediterranean Route: A Legal Analysis of Recent Bilateral Agreements Between Italy and Libya. (26th September 2017) - de Guttry, Andrea; Capone, Francesca; Sommario, Emanuele
Abstract: Dealing with the current flow of migrants flocking to the shores of southern European countries remains high on the international agenda. At the end of 2016, 276, 957 migrants were waiting in Libya to cross the sea. Many of them were subject to human rights violations and abuses such as arbitrary detention, torture, unlawful killings, sexual exploitation and even slavery (IOM, 2017). The international response has been, so far, insufficient and new ideas and practices are urgently needed. After providing an overview of the legal framework and of the efforts carried out by the relevant international and regional organizations, this article focuses on recent treaties concluded between Italy and Libya, and argues that the new bilateral agreements represent an example of how States are responding to this challenge in an attempt to strike a balance between the need to strengthen the protection of migrants' rights and the necessity to guarantee the security of national borders.